2002
DOI: 10.1021/ja0171512
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transfer Reactions on Semiconductor Surfaces

Abstract: The concept of proton affinity on semiconductor surfaces has been explored through an investigation of the chemistry of amines on the Ge(100)-2 x 1, Si(100)-2 x 1, and C(100)-2 x 1 surfaces. Multiple internal reflection Fourier transform infrared (MIR-FTIR) spectroscopy, temperature programmed desorption (TPD), and density functional theory (DFT) calculations were used in the studies. We find that methylamine, dimethylamine, and trimethylamine undergo molecular chemisorption on the Ge(100)-2 x 1 surface throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
316
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(343 citation statements)
references
References 54 publications
23
316
4
Order By: Relevance
“…The imine Ge-N dative bond length is intermediate between amine-like Ge-N dative bonds (2.13-2.18 Å) and a Ge-N covalent bond (1.7 Å). 18 The C-N a , C-N b , and C-N c bond lengths lie between the CdN double bond length (1.28 Å) and the C-N single bond length (1.4 Å) for both conformers. 12 The equivalent Figure 10.…”
Section: Alaninementioning
confidence: 95%
See 3 more Smart Citations
“…The imine Ge-N dative bond length is intermediate between amine-like Ge-N dative bonds (2.13-2.18 Å) and a Ge-N covalent bond (1.7 Å). 18 The C-N a , C-N b , and C-N c bond lengths lie between the CdN double bond length (1.28 Å) and the C-N single bond length (1.4 Å) for both conformers. 12 The equivalent Figure 10.…”
Section: Alaninementioning
confidence: 95%
“…For example, the energetics of the reactions of the common carbonyl, hydroxyl, and amine groups are almost identical to what has been calculated previously on the Si(100)-2×1 surface. 14,18 However, we also identified several mechanisms that had not been previously investigated, especially for the reactions of arginine and histidine. 12 We found that the imine group of arginine's guanidine side chain forms a strong "dative" bond where the imine lone pair acts as a Lewis base and the electrophilic "down" atom of the Si(100)-2×1 surface acts as a Lewis acid.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…A number of (mostly experimental) studies have been accomplished regarding the TMA molecular adsorption on the surfaces of several interesting materials like silicon [37][38][39][40], nickel [41], ruthenium [42] or platinum [43,44]. All these studies illustrate the tendency of the nitrogen atom in TMA to act as a Lewis base and form a dative bond with electron-withdrawing surface atoms.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%